2017
DOI: 10.1007/s11136-017-1727-x
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary report on psychiatric impairments and quality of life among Kaohsiung gas explosion victims 6 months after the event

Abstract: This study shows that probable PTSD/MDE is associated with lower QOL, supporting the need for early mental health rehabilitation after a disaster. Therefore, rapid screening and early mental rehabilitation are very important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(45 citation statements)
references
References 20 publications
3
40
2
Order By: Relevance
“…Current marital status and probable psychiatric diagnosis were statistically significant after a year but were not significantly different compared with those within 6 months [14]. Based on the survey administered at 6 months, 161 respondents (32.1%) had at least one probable psychiatric diagnosis and were assigned to the following groups: probable PTSD (n=54) [10.8%], probable MDE (n=37) (7.4%), or probable PTSD and MDE (n=70) (13.9%) [13].…”
Section: Resultsmentioning
confidence: 69%
See 4 more Smart Citations
“…Current marital status and probable psychiatric diagnosis were statistically significant after a year but were not significantly different compared with those within 6 months [14]. Based on the survey administered at 6 months, 161 respondents (32.1%) had at least one probable psychiatric diagnosis and were assigned to the following groups: probable PTSD (n=54) [10.8%], probable MDE (n=37) (7.4%), or probable PTSD and MDE (n=70) (13.9%) [13].…”
Section: Resultsmentioning
confidence: 69%
“…We found that survivors' psychological trauma, risk factors and QoL were similar at one year after the southern Taiwan Kaohsiung gas explosion compared with six months after the event [14]. Current marital status and probable psychiatric diagnosis were statistically significant after a year but were not significantly different compared with those within 6 months [14].…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations